Extinción Automática del Derecho a los Alimentos Cuando el Beneficiario ha Cumplido la Edad Establecida en la Norma - Ortiz Yaguana, Stiven Estuardo (2022)
This research titled "AUTOMATIC EXTINCTION OF THE RIGHT TO FOOD WHEN THE BENEFICIARY HAS COME OF AGE ESTABLISHED IN THE NORMS". It proposes that the child maintenance be expired by the judge, taking into consideration the only presentation of an application with the enabling documents and the certificate granted by CONADIS that demonstrate that the party sharing of the right to child maintenance is not in a condition of disability, which guarantees respect for the principle of procedural economy includes in the Constitution of the Republic. After having carried out my research work, I conclude that the procedure that is given to the incident of expiration of child maintenance is not adequate because within it several unnecessary procedural steps are carried out, taking into consideration that the only thing that is required for the judge decides to expire the child maintenance is that debtor proves with the qualifying documents that the creditor has ceased to be the party sharing to due to any of the circumstances according to the law, in other words that the reasons for which were fixed the child maintenance have disappeared, which does not happen at present since all procedural acts must be complied with, thus causing an unjustified spending of money, the loss of time of judicial officials, the wastage of the judicial system as well as the accumulation of causes. The proposal of this research is helping to save resources both from the justice system and from who come to it in search of having their rights restored in the most agile and expeditious way as established by the Constitution. According to these parameters, I can conclude that this research work is of vital importance and transcendence, since it seeks to provide an alternative solution, so that the officials of the Family, Women, Children and Adolescents Judicial Units can provide fast and timely attention to users, thus restoring their trust in justice.